2008
DOI: 10.1080/10428190701704605
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of drug-metabolizing enzymesCYP1A1,GSTTandGSTPcontribute to the development of diffuse large B-cell lymphoma risk in the Saudi Arabian population

Abstract: The last four decades have seen significant increase in the incidence of non-Hodgkin lymphoma (NHL) as a possible result of increasing environmental carcinogens exposure. Based on the increasing evidence for the association between carcinogen-exposure-related cancer risk and xenobiotic gene polymorphisms, we have undertaken a hospital based case-control study on xenobiotic gene polymorphisms in Saudi individuals with a diagnosis of diffuse large B-cell lymphoma (DLBCL). Polymorphisms in five genes (CYP1A1, GST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 40 publications
6
29
1
4
Order By: Relevance
“…Calculation of the risk estimate revealed that GSTM1 null genotype was not associated with DLBCL risk. This is in accordance with many previous studies (Al Dayel et al 2008;Sarmanova et al 2001;Kerridge et al 2002;Chiu et al 2005). On the other hand, the study of Gra et al (2002) reported that the GSTM1 null genotype correlates with increased risk of NHL.…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…Calculation of the risk estimate revealed that GSTM1 null genotype was not associated with DLBCL risk. This is in accordance with many previous studies (Al Dayel et al 2008;Sarmanova et al 2001;Kerridge et al 2002;Chiu et al 2005). On the other hand, the study of Gra et al (2002) reported that the GSTM1 null genotype correlates with increased risk of NHL.…”
Section: Discussionsupporting
confidence: 95%
“…In our study, dual null genotype was detected in 23.9 % of DLBCL patients. This is consistent with that previously reported by Al Dayel et al (2008) and Kerridge et al (2002). Dual null genotype was signiWcantly higher in DLBCL patients compared to controls and conferred twofold increase DLBCL risk.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations